PENGATURAN PENDIRIAN RUMAH IBADAH DAN KONFLIK ANTAR UMAT BERAGAMA DI KABUPATEN ACEH SINGKIL - Muhammad Syarif (Al-Ijtima`i: International Journal of Government and Social Science, 2023)
Maintaining religious harmony at the regional, provincial, and central levels is the obligation of all citizens and other government agencies. Islamic law in Aceh actually does not only deal with matters of faith, maisir, khalwat, and khamar, but actually also takes care of all aspects of life including relations between religious adherents. So that the Aceh government issued a form of regulation in the form of Perda No. 25 of 2007 concerning Guidelines for the Establishment of Houses of Worship. The case in Aceh Singkil several years ago shows that religious harmony has not been fully created in Aceh. Therefore, in this discussion conducted an assessment of Islamic views on religious harmony and efforts to overcome inter-religious conflicts. The research results show that rules for religious harmony in Islam are contained in the Medina Charter, while the Republic of Indonesia Law states that the state guarantees the freedom of every citizen to embrace their own religion and to worship according to their religion and beliefs. While the rules related to the establishment of houses of worship in Aceh have also been regulated in the Form of Regional Regulation No. 25 of 2007 concerning Guidelines for the Establishment of Nanggroe Aceh Darussalam Houses of Worship. The conflict between religious communities in Aceh Singkil was caused by the government's lack of attention and its occurrenceclash of wisdom, breach of agreement and regulation, social prejudice, bigotry, and lack of communication. The solution with examine the root causes of conflict, process it in a fair and transparent manner and increase outreach and dialogue between religious leaders.